Development of bee colonies based on early spring feeding according to the developed scheme - Adamchuk, L. O.; Boiarchuk, S. V.; Lavrinenko, K. V.; Dvykaliuk, R. M.; Martseniuk, N. I. (НУБіП України, 2019)
The strength and development of bee colonies in May, especially those that have weakened afer wintering, is not sufficient for the effectve use during the first honey harvest in Ukraine.One way to effectvely stmulate bee colonies to develop is through the use of carbohydrate protein feedings.The purpose of the study was to investigate the development of bee colonies in the early spring with the use of different types of feeding.The studies were conducted using zootechnical (alignment and assessment of the status of bee colonies, control feeding) and statistical methods of research in the early spring of 2019 in the conditions of Holosiivskaapiary (Kyiv, Ukraine). The control group – classic maintenance, similar to all apiary colonies. The research group – was applied the developed scheme of early spring feeding and training of bees. For feeding, honey – beebread dough, bee pollen in the form of flour, monofloral bee pollen candy were used. Afer the first feeding, the experimental colonies outweighed the control ones by 0.3 rows in strength, 0.5 comb by the number of open brood combs and 0.43 comb by the sealed ones as well as by 1.3 comb of fodder (5.3 kg). Afer the second feeding, the experimental colonies outweighed the control ones by 1.6 rows in strength, 1.5 comb by the number of open brood combs, were the same by the number of sealed sells and outweighed by 0.3honeycomb in the number of fodder. During the evaluation it was found that the experimental colonies outweighed the controlled ones instrength by 2 rows, by 0.5 in open and by 1 comb in sealed brood combs as well as by 0.5 honeycomb of fodder (2 kg). It was found that a complex three-stage carbohydrate-protein feeding of weak bee colonies (5–6 combs) after wintering makes it possible to increase their strength to 10 combs by early May.
Розвиток бджолиних сімей внаслідок ранньовесняної підгодівлі за розробленою схемою
Сила і розвиток бджолиних сімей у травні, особливо тих, що ослабли після зимівлі, не достатня для ефективного використання першого медозбору в умовах України. Одним із способів ефективного стимулювання бджолиних сімей до розвитку є використання вуглеводно-білкових підгодівель. Метою роботи було дослідити розвиток бджолиних сімей у ранньовесняний період із застосуванням підгодівлі. Дослідження проводили з використанням зоотехнічних (вирівнювання та оцінка стану бджолиних сімей, контрольна підгодівля, дресерування) та статистичних методів дослідження у ранньовесняний період 2019 року в умовах Голосіївської пасіки (м. Київ, Україна). Контрольна група – класичне утримання, подібне до всіх сімей пасіки. Дослідна група – застосовували розроблену схему ранньовесняної годівлі і дресирування бджіл. Для підгодівлі застосовували медово-пергове тісто, бджолине обніжжя в стані борошна, канді з монофлорного бджолиного обніжжя (як елемент дресирування). Після першої підгодівлі дослідні сім’ї за силою переважали контрольні на 0,3 вулички, за кількістю відкритого стільника переважали на 0,5, а запечатаного – на 0,43 стільника, за кількістю кормів переважали на 1,3 стільника (5,3 кг). Після другої підгодівлі дослідні сім’ї за силою переважали контрольні на 1,6 вулички, за кількістю відкритого – 1,5 стільника, за кількістю критого розплоду були однаковими, за кількістю кормів переважали на 0,3 стільника (1,3 кг). Під час оцінювання встановили, що дослідні сім’ї за силою в кінці експерименту переважали контрольні на 2 вулички, за кількістю відкритого – на 0,5, а запечатаного – на 1 стільник, за кількістю кормів – на 0,5 стільника (2 кг). Встановили, що комплексна триетапна вуглеводно-білкова підгодівля слабких бджолиних сімей (5-6 стільників) після зимівлі дає можливість наростити їх силу до 10 стільників на початок травня.
Keywords: honey dough; candy; sugar syrup; bee brood; медове тісто; канді; цукровий сироп; розплід бджіл